Knovel critical tables (Knovel, 2003)
Contains tables of physical, solvent, and thermodynamic properties.
Title from the resource itself (viewed Feb. 19, 2003).
Keywords: Chemistry -- Tables.; Chemistry, Physical and theoretical -- Tables.; Organic compounds -- Tables.; Chemistry, Inorganic -- Tables.; Thermochemistry -- Tables.; Science -- Tables.; elektronické knihy; electronic books